Pterigión y su relación con la actividad laboral en las edades comprendidas de 20 a 65 años atendidas de la ciudad de Loja, periodo enero a junio 2016. - Chamba Maza, María Fernanda (2017)
The pterygium is a pathology that frequently occurs in the Ophthalmology Consultation of Isidro Ayora Provincial Hospital of Loja, so this paper aims to determine in which age groups has a higher incidence, as well as to know in which gender is more frequent, their relation to their work activity, their relation to other ophthalmological conditions and the predominant degree, between January and June 2016. It is a retrospective - descriptive study in a total of 28 patients that met the inclusion criteria. A questionnaire was applied in response to the specific objectives, which allowed us to obtain the following results: The frequency of pterygium from 20 to 65 years in the 6 months is 9%. This pathology was presented with a greater percentage in age range from 51 to 60 years with 29%; it also predominates in women with 64% compared to 36% in men; in terms of labor activities could be identified: agriculture 21%, trade and household chores with 14%; is associated in greater mayoritary with conjunctivitis, in 24%; ocular trauma and cataract 19%; In addition, grade II predominates with 32%. These findings show both the age and gender range most affected, the absence of preventive measures, which can serve as clinical markers that allow the detection of the disease in early clinical stages and thus prevent its development into more severe forms. Key words: Pterygium, age group, work activity.